An integrative taxonomic study of Pavanelliella spp. (Monogenoidea, Dactylogyridae) with the description of a new species from the nasal cavities of an Amazon pimelodid catfish. Issue 6 (December 2017) - Aguiar, Julio C.; Maia, Antônio A.M.; Silva, Marcia R.M.; Ceccarelli, Paulo S.; Domingues, Marcus V.; Adriano, Edson A.
Abstract: The present study is an integrative taxonomic analysis of Pavanelliella spp. (Monogenoidea, Dactylogyridae), and describes a new species from the nasal cavities of the Amazonian pimelodid catfish Brachyplatystoma rousseauxii (Siluriformes Pimelodidae) from the Tapajós River (Amazon Basin, Pará state, Brazil). Pavanelliella jarii sp. n. is characterized by the presence of 3–4 rings in the male copulatory organ, the absence of rings around the vaginal atrium and by its sinuous vaginal canal, which sometimes forms 0.5–1 rings in the distal portion. The sequencing of the small subunit ribosomal DNA (ssrDNA) and internal transcribed spacer 1 (ITS-1) of three species of Pavanelliella, Vancleaveus cicinnus, and an undetermined dactylogyrid allowed the phylogenetic reconstruction of these dactylogyrids. The analysis indicated that P . jarii sp. n. is closely related to Pavanelliella takemotoi and Pavanelliella pavanellii, which formed a sister clade to ancylodiscoidines parasites of siluriform fish from the Oriental and Afrotropical regions. The analysis also corroborated the non-monophyly of Ancyrocephalinae, revealing that ancylodiscoidines arose between ancyrocephalines lineages, in a sister relationship to pseudodactylogyrines + marine ancyrocephalines + ancyrocephalines parasites of afrotropical perciforms + dactylogyrines. Cladistical analysis indicates that the haptoral anchor/bar complex has been lost several times in the evolutionary history of Dactylogyridae. The analysis also indicated that Dactylogyrus is polyphyletic, as Acolpenteron ureteroecetes and Dactylogyroides longicirrus arose between the three lineages formed by Dactylogyrus spp. Graphical abstract: